P243 A Retrospective Observational Study Of 20 Year Lung Transplant Survivors – A Single Centre Experience. (10th November 2014) - Sithamparanathan, S; Thirugnanasothy, L; Fisher, AJ; Lordan, J; Meachery, G; Dark, JH; Hasan, A; Clark, SC; Gould, K; MacGowan, GA; Parry, G; Corris, PA
Abstract : Introduction and objectives: Lung transplant patients have a reduced survival rate compared to other solid organ recipients. Chronic lung allograft dysfunction (CLAD) remains the main factor in limiting longevity in lung transplant patients, with 50% of recipients developing Bronchiolitis Obliterans Syndrome (BOS) by 5.6 years. There is a lack of published data on the course and history of long term survivors and we describe characteristics and outcomes of all lung transplant recipients who have survived greater than 20 years at our centre. Results: Twenty-one (16.2%) out of a possible total of 121 transplant patients survived at least 20 years with an overall median survival of 21.3 (range 20.1–24.9) years. The mean age at transplantation was 31.8 ± 9.9 years and 13 (61.9%) were male. The most common indication for transplantation in the group was Cystic Fibrosis (33.3%); heart-lung and bilateral lung transplant operations were equally the most commonly performed. The median six-minute walk distance (6MWD) was 600m (range 419–785m). The median time to the development of BOS was 9.7 years. At time of evaluation, 2 (10%) patients had BOS score 0, 3 (14%) BOS 1, 6 (29%) BOS 2 and 10 (48%) BOS 3. The total number of rejections requiring augmentation with corticosteroids was 30 episodes in 21 patients with an average of 1.4 (range 0–3) episodes per patient. Eighteen patients had at least one episode of rejection needing corticosteroids. No patient developed symptomatic ischaemic heart disease; systemic hypertension was found in 19 (90.5%) patients. Two (9.5%) patients developed post-transplant lymphoproliferative disease. Four patients developed other malignancies, 3 of which were skin cancers and 1 renal cancer. All 4 cases of diabetes post transplantation occurred in patients with Cystic Fibrosis. Eight patients required renal replacement therapy as a result of ciclosporin toxicity and four underwent renal transplantation. Conclusion: Twenty-one (16.2%) patients in our cohort survived 20 years. Although nearly all patients developed an element of CLAD, exercise tolerance was preserved as judged by 6MWD. Hypertension was common and renal failure remained the most problematic complication of immunosuppression.